Leveraging everyday technology for people living with dementia: a case study. Issue 4 (9th December 2014) - Astell, A.J.; Malone, B.; Williams, G.; Hwang, F.; Ellis, M.P.
Abstract : Purpose: – The purpose of this paper is to present the self-described "journey" of a person with dementia (Brian; author 3) in his re-learning of old technologies and learning of new ones and the impact this had on his life. Design/methodology/approach: – This is a single case study detailing the participant's experiences collaborating with a researcher to co-create methods of facilitating this learning process, which he documented in the form of an online blog and diary entries. These were analysed using NVivo to reveal the key themes. Findings: – Brian was able to relearn previously used technologies and learn two new ones. This lead to an overarching theme of positive outlook on life supported by person-centredness, identity and technology, which challenged negative perceptions about dementia. Research limitations/implications: – The paper provides an example of how learning and technology improved the life of one person with dementia. By sharing the approach the authors hope to encourage others to embrace the challenge of designing and developing innovative solutions for people with a dementia diagnosis by leveraging both current mainstream technology and creating novel bespoke interventions for dementia. Originality/value: – The personal perspective of a person with dementia and his experiences of (re-) learning provide a unique insight into the impact of technology on his life.